Young children's online learning during COVID-19 pandemic: Chinese parents' beliefs and attitudes. (November 2020) - Dong, Chuanmei; Cao, Simin; Li, Hui
Highlights: Addressed young children's online learning during the pandemic. Added new understanding of parents' beliefs and attitudes around online learning. Identified challenges and issues in promoting online learning during COVID-19. Abstract: Online learning has been widely promoted to replace traditional face-to-face learning during the COVID-19 pandemic to maintain young children's learning and play at home. This study surveyed 3275 Chinese parents' beliefs and attitudes around young children's online learning during the lockdown of the COVID-19 pandemic. Most parents (92.7%) in the study reported that their children had online learning experiences during the pandemic, and many (84.6%) spent less than a half-hour each time. The parents generally had negative beliefs about the values and benefits of online learning and preferred traditional learning in early childhood settings. They tended to resist and even reject online learning for three key reasons: the shortcomings of online learning, young children's inadequate self-regulation, and their lack of time and professional knowledge in supporting children's online learning. Also, the hardship caused by the COVID-19 pandemic has made them suffering, thus more resistant to online learning at home. The results suggested that the implementation of online learning during the pandemic has been problematic and challenging for families. The Chinese parents were neither trained nor ready to embrace online learning. The paper concluded with implications for policymakers and teacher education.